2008
DOI: 10.1021/om7002688
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Photochemically Controlled Crown Ethers: (Tetramethylcyclobutadiene)cobalt Complexes with Benzo-15-Crown-5 and Dibenzo-18-Crown-6

Abstract: The photochemical substitution of benzene in [Cb*Co(C 6 H 6 )] + (Cb* ) C 4 Me 4 ) with benzo-15-crown-5 (1) gives the corresponding π-complexArene exchange is reversible, and both 1 and 3 can be regenerated by irradiation of 2 and 4 with excess benzene. The reaction of [Cb*Co(C 6 H 6 )] + with 0.5 equiv of 3 gives dinuclear complex [trans-Cb*Co(µ-η 6 ,η 6 -C 6 H 4 (OCH 2 CH 2 OCH 2 CH 2 O) 2 C 6 H 4 )CoCb*] 2+ (5). The structures of cations 4 and 5 were confirmed by X-ray diffraction. The electrochemical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The dinuclear tetracation 3 does not bind Na + within measurable limits of NMR titration method (K a < 1 M À1 ). These results indicate that p-coordination of the cationic [(mes)Ru] 2+ fragments decreases the sodium ion binding ability of the benzocrown ethers by several orders of magnitude, presumably due to electrostatic repulsion [7].…”
Section: Nmr Titrationmentioning
confidence: 86%
See 1 more Smart Citation
“…The dinuclear tetracation 3 does not bind Na + within measurable limits of NMR titration method (K a < 1 M À1 ). These results indicate that p-coordination of the cationic [(mes)Ru] 2+ fragments decreases the sodium ion binding ability of the benzocrown ethers by several orders of magnitude, presumably due to electrostatic repulsion [7].…”
Section: Nmr Titrationmentioning
confidence: 86%
“…Recently, we have demonstrated that p-coordination of the [(C 4 Me 4 )Co] + fragment with benzocrown ethers significantly decreases their Na + binding ability [7]. Herein we report the synthesis of (mesitylene)ruthenium p-complexes with benzo-15-crown-5 and dibenzo-18-crown-6 along with their structural, NMR titration, and electrochemical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is presumably a consequence of the presence of the unusual bridging pair of perchlorate anions distorting the structure. This issue was addressed by DFT calculations23,24 using the b3ylp functional and the Lanl2DZ basis set to optimise a monomeric perchlorate structure in the gas phase (Figure 1, b). A frequency calculation confirmed that the optimised geometry was an energy minimum.…”
Section: Resultsmentioning
confidence: 99%
“…The design of functionalized crown ethers is an intensively studied area of tremendous potential significance because of the new properties that can be generated. For example, a common approach in this area is the organometallic functionalization of the classic crown ethers in order to obtain photochemical controlled and electrochemical active receptors or compounds with promising anticancer properties . Furthermore, metalloligands may be defined as compounds with potential coordination sites possessing a metal center in their structure, and they have recently attracted much attention in supramolecular chemistry because the physical and chemical properties of the metal center as well as the characteristic structure of the complex are very useful in obtaining a stronger and more selective recognition, as well as the formation of a stable supramolecular system …”
Section: Introductionmentioning
confidence: 99%